ChemInform Abstract: Alkali Metal — Yttrium Borohydrides: The Link Between Coordination of Small and Large Rare‐Earth. Issue 14 (April 2015) - Sadikin, Yolanda; Stare, Katarina; Schouwink, Pascal; Brix Ley, Morten; Jensen, Torben R.; Meden, Anton; Cern, Radovan
Abstract: The system Li—M—Y—BH4 (M: K, Rb, Cs) contains five new compounds, KY(BH4 )4 (I), RbY(BH4 )4 (II), Rb3 Y(BH4 )6 (III), Cs2 Y(BH4 )5 (IV), and Cs3 Y(BH4 )6 (V) which are characterized by synchrotron powder XRD, FTIR spectroscopy, impedance spectroscopy, and periodic DFT calculations.